2005
DOI: 10.1088/0268-1242/20/7/010
|View full text |Cite
|
Sign up to set email alerts
|

Two-colour diode lasers for generation of THz radiation

Abstract: Direct emission of terahertz (THz) radiation out of a two-colour semiconductor laser is reported and analysed. The geometry of the tunable two-colour laser is described together with the physical mechanisms responsible for the emission at the THz difference frequency of the two pump colours used. On the basis of this analysis, different possibilities are suggested to increase the emitted THz intensity towards application relevant levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…A few years ago, we have shown that two-colour diode lasers emit directly the THz difference frequency of the two colours [16]. We have discussed possible strategies for increasing the generated power via this direct THz generation and our estimations show that with some technological effort into the device design the generated power may reach the µW range and thus become competitive with that of external photomixing systems [17]. To analyse the obtainable bandwidth of this concept, we made use of the fact that the nonlinearity responsible for the direct THz generation also results in the generation of four-wave mixing (FWM) sidebands which are easily visible in the near infrared optical spectra.…”
Section: Direct Thz Generation With Two-colour Lasersmentioning
confidence: 98%
“…A few years ago, we have shown that two-colour diode lasers emit directly the THz difference frequency of the two colours [16]. We have discussed possible strategies for increasing the generated power via this direct THz generation and our estimations show that with some technological effort into the device design the generated power may reach the µW range and thus become competitive with that of external photomixing systems [17]. To analyse the obtainable bandwidth of this concept, we made use of the fact that the nonlinearity responsible for the direct THz generation also results in the generation of four-wave mixing (FWM) sidebands which are easily visible in the near infrared optical spectra.…”
Section: Direct Thz Generation With Two-colour Lasersmentioning
confidence: 98%
“…Accordingly, one has to perform an extensive analysis of means how to improve the experimental setup and, in particular, the diode laser design to achieve application relevant power levels. We now extend the first analysis given in [59] in order to find out whether application relevant power levels in the range above 1 µW can be achieved at all: A first major improvement of the direct emission approach can be achieved with a modification of the cavity geometry of the two color laser. Matus et al have analyzed this laser system theoretically and showed that the spectral purity of the two color emission is crucial for the nonlinear frequency mixing of the two colors [61].…”
Section: Improvement Of Direct Thz Generationmentioning
confidence: 98%
“…Then, the normalized bolometer signal for the operation on one color only is subtracted from the two-color signal to extract the specific contribution due to two-color operation. Further details on this normalization procedure are given in [59]. Our data for the normalized THz signal as a function of the difference frequency ν 21 are shown by the red dots in Fig.…”
Section: Direct Thz Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-wavelength diode laser systems are attractive for many applications, such as dual-wavelength interferometry, optical switching, terahertz (THz) radiation generation, and THz imaging [1][2][3][4][5]. Different techniques have been developed to achieve dual-wavelength operation of a diode laser system, and they mainly can be classified into two categories: (1) Monolithic dual-wavelength diode lasers [6][7][8][9][10], and (2) diode laser systems based on different external-cavity feedback techniques [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%